The Social Loafing Phenomenon - Tayo, Yanti; Nursanti, Siti; Utamidewi, Wahyu; Mayasari; Abidin, Zainal (International Journal of Psychosocial Rehabilitation, 2020)
Social loafing is a behavioral condition when one of the members in a group feels like he only needs to contribute at the very least, while all group members should have an equal amount of work. The phenomenon of social loafing usually occurs in a large group in which the group members have different characteristics. By applying a qualitative method and phenomenological approach, this study aims to observe the motive, meaning, and experience of someone who exhibits social loafing behaviors. The study finds that students with social loafing behaviors have a motive to be a passive member in an existing group. They usually join the groups that are most influential in the classroom in terms of score achievement. Moreover, the communication experience of students with social loafing behaviors is often rejected by their fellow members. They also receive unpleasing treatments most of the time.